The Influence of Pre‐Electrospinning Plasma Treatment on Physicochemical Characteristics of PLA Nanofibers. Issue 11 (8th November 2019) - Rezaei, Fatemeh; Planckaert, Tom; Vercruysse, Chris; Verjans, Jente; Van Der Voort, Pascal; Declercq, Heidi; Hoogenboom, Richard; Morent, Rino; De Geyter, Nathalie
Abstract : Back Cover : In article number 1900391 by Fatemeh Rezaei and co‐workers, poly lactic acid (PLA) spinning solutions in chloroform and 5, 5‐ N ‐dimethylformamide are exposed to pre‐electrospinning plasma treatment (PEPT). Physicochemical properties of the resultant PLA nanofibrous materials are carefully examined by using a wide range of analysis methods, including SEC, DSC, TGA, XRD, XPS, SEM and mechanical testing. It is revealed that the physicochemical properties of the nanofibers are significantly enhanced after PEPT.